The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fcimb.2021.710551
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Continuous Flavivirus Epitopes From Naturally Infected Humans

Abstract: This manuscript is an up-to-date review of experimentally validated linear and continuous epitopes identified from arbovirus members of the Flavivirus genus. We summarized 153 immunoreactive peptides from the Dengue virus, Zika virus, Japanese encephalitis virus, West Nile virus, and tick-borne encephalitis virus described in studies published from 1989 to 2020. We included peptides from structural (envelope, capsid, and pre-membrane) and nonstructural (Ns1–5) viral proteins that demonstrated relevant immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Peptides have shown significant potential in advancing the development of highly specific diagnostic tests and vaccines [ 16 18 ]. In the present study, we unveiled the epitope profile recognized by dengue and Zika patients in the E and NS1 proteins of both DENV and ZIKV, highlighting certain peptides that show promise for the development of serological tests for the differential diagnosis of dengue and Zika infections, as well as for the production of candidate vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides have shown significant potential in advancing the development of highly specific diagnostic tests and vaccines [ 16 18 ]. In the present study, we unveiled the epitope profile recognized by dengue and Zika patients in the E and NS1 proteins of both DENV and ZIKV, highlighting certain peptides that show promise for the development of serological tests for the differential diagnosis of dengue and Zika infections, as well as for the production of candidate vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…For 2F2 mAb, the reactively identified epitopes were mostly conserved between ZIKV, DENV, WNV, and JEV in both linear and structural aspects. Previous studies have identified similar linear and discontinuous flavivirus epitopes from naturally infected humans [ 49 ]. The epitope REGYRT mapped on immunodominant region three of the NS1 loop has been previously described [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe the improved specificity of the pAbs in rabbit sera was conferred by the use of the C-terminal fragment of ZIKV-NS1 as the background for finding specific reactive epitopes [ 26 , 47 ]. We checked six distinct regions for highly reactive ZIKV, and only one region was detected with less intensity for DENV and YFV [ 49 ]. The ZIKV epitope EGYRTQV is located from immunodominant region three to the loop and from the epitopes LRSTTASGR (ZIKV) SLRTTTASG (DENV2), SLRTTTVSG (DENV3) to the immunodominant region four [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to hyperinflammatory responses and cytokine storms, potentially causing lethal dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS) [ 16 , 18 , 19 ]. Antibodies against the ZIKV E protein also carry the risk of exacerbating DENV symptoms via ADE as the E proteins of the two flaviviruses share many common epitopes [ 20 , 21 ]. Indeed, the ADE of DENV infection and disease severity through anti-ZIKV antibodies have been demonstrated both in vitro and in vivo [ 15 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%